Penciptaan Naskah Drama Bacakak Terinspirasi Konflik Adat Minangkabau Sumatera Barat - INDRA ARDIYANTO (Saraswati)
Bacakak plays is a realist plays against a backdrop of indigenous conflict that occurred in Minangkabau of West Sumatra . Bacakak is a term in the language of Minangkabau which means fighting . The battle over land occurred in the Ervan’s family caused by inherited land which falls on the sister neglected and abandoned . Until Aaron intends sold and it is one form of customs violations , because to sell a customary land must be with the permission of the heir is female .Bacakak plays wealth was created to fill a play realist backdrop of conflict with indigenous Minangkabau culture . Realist is the one who in every respect rests on the fact , rather than thinking . According to the RMA . Harymawan realism in general is the art of trying to achieve a flow of illusion over the depiction of reality .The end result plays Bacakak creation has a deep message in it . Therefore the nomads should not forget his hometown and also as a reflection of the traditional rules that should not be violated.Keywords : Indigenous , realist , message